Dictyostelium discoideum as a Model for Investigating Neurodegenerative Diseases - Haver, Holly N.; Scaglione, K. Matthew (Frontiers in Cellular Neuroscience, 2021)
The social amoeba Dictyostelium discoideum is a model organism that is used to investigate many cellular processes including chemotaxis, cell motility, cell differentiation, and human disease pathogenesis. While many single-cellular model systems lack homologs of human disease genes, Dictyostelium’s genome encodes for many genes that are implicated in human diseases including neurodegenerative diseases. Due to its short doubling time along with the powerful genetic tools that enable rapid genetic screening, and the ease of creating knockout cell lines, Dictyostelium is an attractive model organism for both interrogating the normal function of genes implicated in neurodegeneration and for determining pathogenic mechanisms that cause disease. Here we review the literature involving the use of Dictyostelium to interrogate genes implicated in neurodegeneration and highlight key questions that can be addressed using Dictyostelium as a model organism.